Analisis Motivasi Berprestasi Siswa sebagai Fondasi “Madrasah Berprestasi” di MAN 1 Lombok Timur: Penelitian - Arroyan, Muhammad Rizki; Hadi, Hasrul; Haerani, Cici; Zohrah, Siti; Zenandi, Reno; Agustina, Widiya Ayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the level of Achievement Motivation (MB) of students at MAN 1 East Lombok, which is an important foundation in realizing the vision of an “Achieving Madrasah”. The main objective is to analyze and map the level of student achievement motivation. The method used is quantitative descriptive with a survey design. The study population included students in grades X, XI, and XII, with samples taken through proportional sampling techniques. Data were collected using questionnaires and analyzed using descriptive percentage analysis. The results showed that student achievement motivation was in the “High” category. This finding reflects a combination of intrinsic motivation in the form of strong academic ideals and extrinsic motivation such as parental and school expectations. It is concluded that high student achievement motivation is an important psychological capital for MAN 1 East Lombok to achieve and maintain the title of “Achieving Madrasah”. The implication is that madrasas need to maintain the sustainability and standardization of motivation strengthening through challenging enrichment programs and a transparent and accountable achievement appreciation system.